Nanotechnology-Based Vaccines - Mohamed Hussein; Madiha Mumtaz; Iqra Nasir; Anisa Abdullahi (Biology, Medicine, & Natural Product Chemistry, 2023)
Several new infectious diseases have developed in recent years, and a few old ones that were formerly thought to pose no threat to humans have made a comeback. Millions of fatalities are attributed to these illnesses together, having a significant negative influence on the worldwide socioeconomic and healthcare sectors. The lack of appropriate medications for many of these disorders is one of the biggest obstacles to treating them. Yet, several of the most common diseases currently have no vaccinations that are reliable. The ideal vaccine should have several key characteristics, including safety, stability, and the capacity to induce a sufficient and long-lasting immune response with a minimal number of doses. To induce protective immunity against illnesses, different generation vaccines are employed, including attenuated or dead entire organisms (first generation), subunits (second generation), and RNA or DNA vaccines (third generation). To get beyond these obstacles, a reliable vaccination delivery mechanism is needed, one that not only gets the vaccine molecules to the target region where they can trigger long-lasting immune responses but also has few side effects and uses fewer doses. Only a few hundred atoms make up the majority of nanoparticles. Nanoparticles have a relatively significant surface area-to-volume ratio because of their extremely small size. Nanoparticles can have surprising optical, physical, and chemical properties due to this property. Nanotechnology has many benefits for the creation of vaccines for the next generation. A delivery strategy based on nanocarriers can shield vaccines from early deterioration, increase stability, have high adjuvant qualities, and can help with the targeted distribution of an immunogen. The researcher conducts an examination of articles that are in accordance with the issue to be studied. Articles used in the literature review are obtained through the database of international journal providers through PubMed, we investigated clinical studies and discussed what happened in these clinical studies and the extent of the effectiveness of Nanoparticle-Based Vaccines. In order to achieve effective vaccine distribution and generate the required host immunity against infectious diseases, this review article focuses on the applications of nanocarrier-based vaccine formulations and the methodologies utilized for functionalizing nanoparticles.